Efek ekstrak daun sirsak (Annona muricata Linn) terhadap profil lipid tikus putih jantan (Rattus Norvegicus) - Wurdianing, Indrawati; Nugraheni, SA; Rahfiludin, Zen (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2014)
Background: Lipid profile effects is a risk factor for Coronary Heart Disease. Soursop leaves (Annona muricata L) isa traditional medicine plant containing metabolic compounds that contribute to the improvement of the lipid profile.Objective: To determine the effects of soursop leaves extract on lipid profile (total cholesterol, LDL cholesterol, HDLcholesterol and triglyceride).Methods: An experimental study using randomized pre-posttest with control group design. Sample consisted of 28 maleWistar rats, were divided into four groups. The control group (K) was only given High Fat High Cholesterol (HFHC)diet and treatment groups (P1, P2, P3) were given a HFHC diet plus Annona muricata L extract with doses of 100, 200and 300 mg/kgBB per day for 28 days respectively. Data were analyzed by Wilcoxon test, Kruskal-Wallis and MannWhitney.Results: The mean total cholesterol level significantly decreased in the treatment group P1 (p = 0.028) from 60.7 mg/dl(47.6-75.3) to 45.5 mg/dl (38.4-62.4). Mean HDL cholesterol level significantly increased in the treatment group P2(p=0.043) from 26.0 mg/dl (19.7-35.3) to 27.9 mg/dl (18.8-38.0). The mean levels of LDL cholesterol and triglyceridedecreased but not significantly.Conclusion: The administration of Annona muricata L extract can decrease total cholesterol and increase HDLcholesterol significantly.